The development of competency frameworks in healthcare professions: a scoping review - Batt, Alan M.; Tavares, Walter; Williams, Brett (Advances in health sciences education : theory and practice, 2020)
Competency frameworks serve various roles including outlining characteristics of a competent workforce, facilitating mobility, and analysing or assessing expertise. Given these roles and their relevance in the health professions, we sought to understand the methods and strategies used in the development of existing competency frameworks. We applied the Arksey and O’Malley framework to undertake this scoping review. We searched six electronic databases (MEDLINE, CINAHL, PsycINFO, EMBASE, Scopus, and ERIC) and three grey literature sources (greylit.org, Trove and Google Scholar) using keywords related to competency frameworks. We screened studies for inclusion by title and abstract, and we included studies of any type that described the development of a competency framework in a healthcare profession. Two reviewers independently extracted data including study characteristics. Data synthesis was both quantitative and qualitative. Among 5710 citations, we selected 190 for analysis. The majority of studies were conducted in medicine and nursing professions. Literature reviews and group techniques were conducted in 116 studies each (61%), and 85 (45%) outlined some form of stakeholder deliberation. We observed a significant degree of diversity in methodological strategies, inconsistent adherence to existing guidance on the selection of methods, who was involved, and based on the variation we observed in timeframes, combination, function, application and reporting of methods and strategies, there is no apparent gold standard or standardised approach to competency framework development. We observed significant variation within the conduct and reporting of the competency framework development process. While some variation can be expected given the differences across and within professions, our results suggest there is some difficulty in determining whether methods were fit-for-purpose, and therefore in making determinations regarding the appropriateness of the development process. This uncertainty may unwillingly create and legitimise uncertain or artificial outcomes. There is a need for improved guidance in the process for developing and reporting competency frameworks.